Panpsychism and the religious attitude - Clarke, D. S. (David S.), 1936- (State University of New York Press, 2003)
"Human beings have thoughts, sensations, and feelings and think that at least some of this mental life is shared with domestic and wild animals. But, are there reduced degrees of mentality found in mosquitoes, bacteria, and even more primitive natural bodies? Panpsychists think so and have defended this belief throughout the history of philosophy, beginning with the ancient Greeks and continuing into the present. In this book, D.S. Clarke outlines reasons for accepting panpsychism and defends the doctrine against its critics. He proposes it as an alternative to the mechanistic materialism and humanism that dominate present-day philosophy."--Jacket